Crystal structure of poly[(μ2-1-(1-imidazolyl)-4-(imidazol-1-ylmethyl)benzene-κ2N:N′)-(μ3-pyridazine-4,5-dicarboxylate-κ3O:O′:N)]copper(II) hydrate, C19H16CuN6O5 - Liu Guang-Zhen; Wang Xiu-Jin; Wei Wen-Hui (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C19H16CuN6O5, triclinic, P1‾$P\overline{1}$ (no. 2), a = 9.0143(3) Å, b = 9.2122(3) Å, c = 11.8205(4) Å, α = 82.900(3)°, β = 74.593(3)°, γ = 83.612(3), V = 935.90(5) Å3, Z = 2, Rgt(F) = 0.0284, wRref(F2) = 0.0684, T = 293 K.